2011
DOI: 10.1063/1.3574343
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of nonlinear waves in compressing plasma

Abstract: Through particle-in-cell simulations, the evolution of nonlinear plasma waves is examined in one-dimensional collisionless plasma undergoing mechanical compression. Unlike linear waves, whose wavelength decreases proportionally to the system length L(t), nonlinear waves, such as solitary electron holes, conserve their characteristic size D during slow compression. This leads to a substantially stronger adiabatic amplification as well as rapid collisionless damping when L approaches D. On the other hand, cessat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…(For WTP parallel compression, see Ref. [96].) Then k remains fixed, so the ACT yields I/n = const, or…”
Section: Nonlinear Action Conservationmentioning
confidence: 99%
“…(For WTP parallel compression, see Ref. [96].) Then k remains fixed, so the ACT yields I/n = const, or…”
Section: Nonlinear Action Conservationmentioning
confidence: 99%
“…Recently, however, a number of studies [11][12][13][14][15] of waveparticle interactions in nonstationary plasmas has revealed previously unexplored phenomenology and potentially useful mechanisms. Such phenomena are intrinsically non-steady-state, and hence require a modification of the methods typically used to analyze and describe the physics in stationary systems.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14] from the work done on current drive schemes in other time-varying conditions, e.g., during plasma current ramp-up in tokamaks, where the current and magnetic field are time-varying [16][17][18][19][20][21], is the direct influence of the time-variation on wave-particle processes in the plasma. Time variation in neither the application of rf power nor changes in the current or poloidal magnetic field alters the underlying wave dynamics or the particle collisionality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the averaged-Lagrangian theory of Refs. [11][12][13] renders analytical transparency, while, numerically, one-dimensional (1D) particle-in-cell (PIC) simulations are distinctly enlightening [7,[16][17][18]. Below we combine these tools to explore the dynamics of BGK-like waves in time-evolving plasma, which exhibit a host of interesting paradigmatic phenomena.…”
mentioning
confidence: 99%